Effects of exercise modalities on decreased blood pressure in patients with hypertension - Ramis, Thiago Rozales; Boeno, Franccesco Pinto; Leal-Menezes, Rodrigo; Munhoz, Samuel Vargas; Farinha, Juliano Boufleur; Ribeiro, Jerri Luiz; Reischak-Oliveira, Alvaro (Frontiers in Physiology, 2022)
This study aimed to evaluate the acute effects of aerobic and resistance exercises on blood pressure and endothelial blood markers. We also correlated post-exercise blood pressure response with baseline cardiovascular parameters in middle-aged patients with hypertension. This cross-sectional study randomized 54 volunteers into: aerobic exercise group (AG, n=27; 45.6±7.7 years) or dynamic resistance exercise group (RG, n=27; 45.8±8.4 years). Blood markers, cardiopulmonary exercise tests, resting blood pressure, ambulatory blood pressure monitoring (ABPM), flow-mediated dilatation, and body composition were evaluated. Exercise sessions were performed to evaluate post-exercise hypotension (PEH) and endothelial marker responses, in addition to post-exercise ABPM (ABPMex). This study is an arm of the study which was approved by the local Ethics Committee (Nº:69373217.3.0000.5347) in accordance with the Helsinki declaration and was registered at ClinicalTrials.gov (NCT03282942). The AG performed walking/running at 60% of the reserve heart rate, while RG performed 10 exercises with two sets of 15-20 repetitions. The mean 24-h ABPM and ABPMex values showed no significant statistical differences. Systolic and diastolic blood pressure hypotension after aerobic and dynamic resistance were -10.59±5.24 / -6.15±6.41 mmHg and -5.56±7.61 / -6.20±8.25 mmHg, respectively. For an up to 7-h assessment of resting pressure, there was a positive effect in the aerobic group. The concentrations of nitrites/nitrates (NOx) and endothelin-1 (ET-1) did not change during hypotension. Moreover, PEH and ABPMex were significantly correlated with baseline health variables. Thus, when middle-aged patients with hypertension perform aerobic or resistance exercise, the NOx/ET-1 pathway does not provide the best explanation for PEH. Finally, we found associations between baseline cardiovascular variables and endothelial vasoconstrictors with PEH.